-2x-1=5(4x+5)-4

Simple and best practice solution for -2x-1=5(4x+5)-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x-1=5(4x+5)-4 equation:


Simplifying
-2x + -1 = 5(4x + 5) + -4

Reorder the terms:
-1 + -2x = 5(4x + 5) + -4

Reorder the terms:
-1 + -2x = 5(5 + 4x) + -4
-1 + -2x = (5 * 5 + 4x * 5) + -4
-1 + -2x = (25 + 20x) + -4

Reorder the terms:
-1 + -2x = 25 + -4 + 20x

Combine like terms: 25 + -4 = 21
-1 + -2x = 21 + 20x

Solving
-1 + -2x = 21 + 20x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-20x' to each side of the equation.
-1 + -2x + -20x = 21 + 20x + -20x

Combine like terms: -2x + -20x = -22x
-1 + -22x = 21 + 20x + -20x

Combine like terms: 20x + -20x = 0
-1 + -22x = 21 + 0
-1 + -22x = 21

Add '1' to each side of the equation.
-1 + 1 + -22x = 21 + 1

Combine like terms: -1 + 1 = 0
0 + -22x = 21 + 1
-22x = 21 + 1

Combine like terms: 21 + 1 = 22
-22x = 22

Divide each side by '-22'.
x = -1

Simplifying
x = -1

See similar equations:

| x+34=5(x+1)-3 | | -8x+20=-2x+44 | | 9m-11=61 | | 5x+33=4(3x-3)+3 | | -3.4q=-4.6-1.1q | | -18=2(3x+3) | | -14=2(4x-2)-2 | | 4x-14=2(4x-3) | | 8=2(x+4)-10 | | 2x-47=3(3x+3) | | 4(5x-1)+6=-2x-42 | | 4(2x+5)=-2x+30 | | x(x+8)=x | | 2(4x-4)=3x+32 | | 5(x+3)-1=-41 | | -2x-12=2(3x-5)+6 | | 2x-42=4(2x-3) | | 3(4x+4)=5x+40 | | -4x-2=-2x+0 | | -3x-30=-4x-34 | | 3(x+3)-10=-3x+35 | | -3x+47=3(4x-2)+8 | | 2x-33=5(4x-1)-10 | | 5x-32=-17 | | 1=3(x+3)-5 | | -39=3(x-5) | | 5(2x+5)=-2x+49 | | x+14=2(2x+2)+1 | | 2(5x+1)=5x-8 | | 4(x+2)-2=-x+41 | | 7=3(x+1)+1 | | B=5n+15 |

Equations solver categories